Cross-species analysis of genetic architecture and polygenic risk scores for non-contact ACL rupture in dogs and humans - Mehdi Momen; Hannah K. Kearney; Margaret M. Patterson; Susannah J. Sample; Zijie Zhao; Qiongshi Lu; Guilherme J. M. Rosa; Peter Muir (Communications Biology)
Abstract Non-contact anterior cruciate ligament (ACL) rupture is a common serious orthopaedic disease in humans and dogs. Familial risk has been recognized in both species but interactions between genetic effects and environmental risk are not understood. We investigated ACL rupture heritability, genetic architecture, selection pressure, sharing of risk genes and biological pathways, and polygenic risk score (PRS) prediction of disease risk. In both species, ACL rupture has moderate heritability, is likely under negative selection, and has a highly polygenic architecture where thousands of variant effects act together to influence disease risk. In dogs, we found hotspots of regional heritability. We also confirmed sharing of multiple risk genes. Our findings challenge the dogma that non-contact ACL rupture is predominantly due to a single overload injury event. Our results also suggest that accurate PRS prediction of ACL rupture risk is an achievable goal in both species, enabling identification of individuals for personalized medical care.